HIGHLIGHTING WOMEN'S EQUALITY AND INJUSTICE IN LITERATURE - Nurweni Saptawuryandari (Himpunan Sarjana-Kesusastraan Indonesia (HISKI), 2021)
Equality is the same thinking between men and women to hold fast to their lives. In fact, equality in feminism is related to gender equality between men and women who have the same position in any case, one of which is work. Therefore, this study aims to reveal (1) how equality and injustice against women are reflected in literary works, especially the novel